2020
DOI: 10.3390/math8030429
|View full text |Cite
|
Sign up to set email alerts
|

Derived Hyperstructures from Hyperconics

Abstract: In this paper, we introduce generalized quadratic forms and hyperconics over quotient hyperfields as a generalization of the notion of conics on fields. Conic curves utilized in cryptosystems; in fact the public key cryptosystem is based on the digital signature schemes (DLP) in conic curve groups. We associate some hyperoperations to hyperconics and investigate their properties. At the end, a collection of canonical hypergroups connected to hyperconics is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
(41 reference statements)
0
7
0
Order By: Relevance
“…In Reference [12], it is shown that the four fundamental relations defined on hyperrings are not equal in general, but for all m-idempotent Krasner hyperrings, it holds Γ = ε m = ξ m = α. Moreover, it is proved that ξ m = α on m-idempotent hyperrings satisfying relation (2), which states that the relation ξ * m is a new representation for the α * -relation on m-idempotent hyperrings satisfying relation (2).…”
Section: Preliminaries On the ξ M -Relation On Hyperringsmentioning
confidence: 97%
See 3 more Smart Citations
“…In Reference [12], it is shown that the four fundamental relations defined on hyperrings are not equal in general, but for all m-idempotent Krasner hyperrings, it holds Γ = ε m = ξ m = α. Moreover, it is proved that ξ m = α on m-idempotent hyperrings satisfying relation (2), which states that the relation ξ * m is a new representation for the α * -relation on m-idempotent hyperrings satisfying relation (2).…”
Section: Preliminaries On the ξ M -Relation On Hyperringsmentioning
confidence: 97%
“…The quotient R/α * is always a commutative ring [15], while the quotient R/ξ * m is not commutative in general [12]. Actually, if (R, +, •) is an m-idempotent hyperring satisfying relation (2), then ξ * m is the smallest strongly regular equivalence relation on R such that the quotient R/ξ * m is a commutative ring. In Reference [12], it is shown that the four fundamental relations defined on hyperrings are not equal in general, but for all m-idempotent Krasner hyperrings, it holds Γ = ε m = ξ m = α.…”
Section: Preliminaries On the ξ M -Relation On Hyperringsmentioning
confidence: 99%
See 2 more Smart Citations
“…If both, the addition and the multiplication, are hyperoperations with the additive part being a canonical hypergroup, then we have superrings [5], which were introduced by Mittas in 1973 [6]. Until now, the most well known and studied type of hyperrings is the Krasner hyperring, that has a plentitude of applications in algebraic geometry [7,8], tropical geometry [9], theory of matroids [10], schemes theory [11], algebraic hypercurves [12,13], hypermomographies [14]. In addition, the theory of hypermodules was extensively investigated by Massouros [15].…”
Section: Introductionmentioning
confidence: 99%